International law and domestic legal systems : incorporation, transformation and persuasion - Shelton, Dinah (OUP OxfordGB, 2011)
Addresses the hierarchy of legal sources within countries, the major sources of international law, treaty and custom, other sources of law and the use of non-binding norms as persuasive authority. Discusses the specific relationship between international law and federal systems. Identifies the similarities and differences among the states presented and their relationship to the increasingly complex international legal systems.